THE DESIGN OF SOLAR DRYING TOOL WITH A FLAT CHIP COLLECTORS - Hizami Ch Anwar; Budianto Lanya; Agus Haryanto; Tamrin - (The University of Lampung, 2012)
Rack solar drier is one example of useful utilization of solar energy, but has not widely used by the public, yet. Using this solar drier we can dry our fish and agricultural products without fossil fuels. Solar dryer works by absorbing sunlight by four blackened flat collectors, and the heat generated by the collectors was transferred by air flow to the plenum chamber and drying chamber consisting of shelves. The solar dryer used in this experiment has dimension of 4,66 m length by 4,66 m width and by 1,95 m height. The dryer has a capacity of around 50 kg materials that can be dried during 20 hours. Based on our testing it was observed that the decrease in water level was not uniform among the shelves position. The final moisture content was highest in the top shelves, followed by middle shelves and bottom shelves. The average final moisture content was 16,95%. The time required for drying was 20 hours, with an average moisture load of 10,46 kg H2O. The average drying rate was 0,5228 kg H2O/jam or 2,10% wet basis per hour. In this experiment intensity of solar radiation was measured to be 634,88 Watt/m2, and electric power of 12,83 Watt was used to run small fan in order to exhaust moist air. The average energy used (Qe) for drying banana chips was 37124,58 kJ per each drying process and the average energy input used during the drying process (Qrs) was 147.227,87 kJ. This meant that average drying efficiency was 27,07%. Technically, it can be concluded that solar dryer can be used as an alternative to drying agricultural commodities. Keywords: moisture content, banana chip, solar drier, flat collectors, solar intensity.